Penerapan Literasi Membaca dan Numerasi Bagi Anak Sekolah Dasar : Penerapan Literasi Membaca dan Numerasi Bagi Anak Sekolah Dasar - Anugrahana, Andri; Pamekas, Yugara (UNIB Press, 2024)
This study aims to describe the implementation of the School Literacy Movement program at the elementary school level in one of the districts in Yogyakarta and to identify the challenges faced. Using a qualitative approach, this study involved 16 teachers in Bantul Regency as research subjects, representing various sub-districts. Data was collected through questionnaires, interviews, and documentation, then analyzed descriptively qualitatively. The results showed that the School Literacy Movement has been implemented comprehensively in the schools studied, focusing on three main aspects: literacy, numeracy, and digital literacy. Common challenges faced include a lack of resources, insufficient teacher training, and limited time. Teachers have tried to overcome these challenges by utilizing technology such as digital books to enrich learning materials. This study concludes that the School Literacy Movement has made a positive contribution to improving students' literacy skills, but there is a need for better support from various parties to overcome the existing challenges.